Hot melt extrusion: An industrially feasible approach for casting orodispersible film - Rushiraj Jani; Dasharath Patel (Elsevier, 2015)
Over the recent few decades, many groups of formulation scientists are concentrating on rapid release dosage forms in oral cavity. Among all fast release dosage forms, orodispersible films are successful to attract pharmaceutical industry due to ease of formulation and extension patent life. Films are popular in patients too because of quick onset and user friendliness of dosage form. From the beginning, solvent casting has been selected as method of choice for manufacturing of orodispersible films. Solvent casting has been proved as a benchmark technology because of ease in product development, process optimization, process validation and technology transfer to production scale despite of some drawbacks like more number of unit operations involved and consumption of large quantity of solvents with controlled limits of organic volatile impurities in final formulation. The application of hot-melt extrusion (HME) in the pharmaceutical industry is consecutively increasing due to its proven innumerable advantages like solvent free continuous process with fewer unit operations and better content uniformity. Very few development activities has been initiated in the field of hot melt extruded orodispersible films so far. This extensive review covers detailed discussion of heavy duty industrial extruders, selection of downstream equipments, selection of excipients, common problems found in formulations and their remedies. Successive part of review addresses identification of critical quality attributes, quality target profile of product, criticality in selection of process parameters and material for substantial simulation in laboratory scale and production for successful technology transfer.